POLITIK HUKUM PEMERINTAH DALAM PENANGANAN TINDAK PIDANA PERIKANAN (ILLEGAL FISHING) DI INDONESIA - Mawardi Khairi (Fiat Justisia: Jurnal Ilmu Hukum, 2016)
The demand for changes in law sector (political law), particularly in maritime and fishery sector, have the consequences of changes to happen. Thus, can be observed for the last 24 years (1985-2014) and has been changed twice, respectively, Law Number 9 of 1985 on Fishery, Law Number 31 of 2004 on Fishery and Law Number 45 of 2009 on Fishery. The changes shows that laws are made to suit society needs and social development, based on theories and law changer aspect. Fishery crime in Indonesia’s territory are dominated by IUU fishing (Illegal, Unreported and Unregulated Fishing). The even rising number of illegal fishing crime that caused financial less to Indonesia has made the government to produce law instruments outside of laws concerning fishery in order for enforcement of law and justice. Keywords : political law, law enforcement, and illegal fishing